Feminist Research into Gendered Violence - Elisabet Le Roux; Selina Palm (African Journal of Gender and Religion (AJGR))
Researching violence, especially within homes, families or closed community spaces, is often challenging. PhotoVOICE 2.0 is an innovative technology-assisted adaptation of the participatory arts-based research (PABR) method, Photovoice. It was developed and piloted in 2018 by the authors to conduct research on the ways the Anglican Mothers’ Union in Zambia contributes to and/or resists violence against women and violence against children. This article discusses the methodological underpinnings and origins of this method and offers an overview of its implementation in Zambia. Several key insights emerge regarding how PhotoVOICE 2.0 enables feminist, participatory arts-based research, including that it empowers local community co-researchers and amplifies the voices of insiders to the specific institution being researched in ways that can support feminist research aims for social transformation. The technological component of the method centers PABR methods throughout the whole research process. The article concludes by emphasizing the extraordinary disruptive power of the PhotoVOICE 2.0 method in subverting existing hierarchies of knowledge and control and highlighting its continued evolution in new settings.